Geoheritage Potential of Limestone Caves at Felda Chiku 7, Gua Musang, Kelantan, Malaysia (Journal of Tropical Resources and Sustainable Science (JTRSS), 2025)
This study aims to assess the geoheritage potential of Felda Chiku 7 in Gua Musang District, Kelantan. The study area hosts two limestone caves, which exhibit distinctive geological and geomorphological features, including karst landforms, speleothems, and speleogens. Geologically, the area is underlain by three primary lithologies — limestone, phyllite, and slate — that comprise the Gua Musang Formation. The geology of the study area is mainly composed of three lithologies: limestone, phyllite, and slate. The study integrated qualitative and quantitative assessments: the qualitative assessment was based on the author's fieldwork observations, whilst the quantitative assessment was based on the Modified Geosite Assessment Model (M-GAM) framework. The M-GAM frameworks integrate expert perceptions with visitors'/public perceptions, with the Main Values covering scientific, aesthetic, and protection values, and the Additional Values covering functional and touristic values. The qualitative assessment indicates the geodiversity of rocks (lithologies), geomorphology (speleothems and speleogens), landscape and fossil. In addition, the scopes are petrological, geomorphological and paleontological sites, and the scale is small. As for the quantitative assessment, the study shows that aesthetic values rank highest, followed by protection, scientific, functional, and tourism values. The M-GAM results indicate an intermediate overall geoheritage potential (28.4%), with exceptionally high scenic/aesthetic and protection scores, and low touristic readiness (restaurant/visitor infrastructure minimal)—consistent with local familiarity but limited public exposure. The findings demonstrate that Felda Chiku 7 holds substantial potential for future geoconservation and geotourism initiatives, provided that appropriate management strategies, interpretative programmes, and community engagement efforts are implemented to enhance accessibility and long-term protection of this natural asset.
Keywords: Geoheritage; Geology; Felda Chiku 7; M-GAM